2014
DOI: 10.1183/09031936.00043814
|View full text |Cite
|
Sign up to set email alerts
|

Mortality risk prediction in COPD by a prognostic biomarker panel

Abstract: Chronic obstructive pulmonary disease (COPD) is a complex disease with various phenotypes. The simultaneous determination of multiple biomarkers reflecting different pathobiological pathways could be useful in identifying individuals with an increased risk of death.We derived and validated a combination of three biomarkers (adrenomedullin, arginine vasopressin and atrial natriuretic peptide), assessed in plasma samples of 385 patients, to estimate mortality risk in stable COPD. Biomarkers were analysed in comb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
32
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 61 publications
2
32
0
2
Order By: Relevance
“…All models included a strong association between age and mortality, which was in line with studies found in the literature [32,33,[35][36][37][38]. Validation against trial results also showed a difference in 12 mortality between young and old patients for the trial as well as most models.…”
Section: Discussionsupporting
confidence: 69%
See 2 more Smart Citations
“…All models included a strong association between age and mortality, which was in line with studies found in the literature [32,33,[35][36][37][38]. Validation against trial results also showed a difference in 12 mortality between young and old patients for the trial as well as most models.…”
Section: Discussionsupporting
confidence: 69%
“…The difference in mortality is less clear from the literature. Some studies reported lower mortality rates for females [32][33][34], while others found no difference [35][36][37][38]. Only two models specified quality of life by gender, while several studies found a lower quality of life for female patients [39][40][41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…acute coronary syndrome [45]. Altogether, several studies found some prognostic value of cardiac biomarkers in stable or exacerbated COPD, individually or as part of a panel [46]. In a previous study, STOLZ et al [47] found that adrenomedullin increases the predictive ability of the BODE index, while combining this biomarker to the BOD (body mass index, FEV1 and dyspnoea) components of the BODE index provided better discrimination than the BODE index itself, therefore alleviating the need for a 6-min walk test.…”
Section: Cardiovascular Biomarkers In Copdmentioning
confidence: 99%
“…While the mechanisms explaining these unique phenotypes or the relationship between COPD and extrapulmonary comorbidities remain a mystery, clearly the notion of a single laboratory test capturing this diversity is hard to endorse. In this issue, STOLZ et al [10] have successfully rectified some of the past shortcomings of biomarker research by broadening the approach to biomarkers, which may have previously been too confined to allow for success. The authors have studied a panel of three biomarkers (adrenomedullin, arginine-vasopressin and atrial natriuretic peptide) in patients with stable COPD, revealing that elevations in all three biomarkers are associated with a five-fold increased risk of death.…”
mentioning
confidence: 99%